2022
DOI: 10.1111/psyp.14183
|View full text |Cite
|
Sign up to set email alerts
|

The diving response and cardiac vagal activity: A systematic review and meta‐analysis

Abstract: In recent years, the diving response has received remarkable attention regarding improving mental health and well-being (Pubmed search "diving response" from 0 to 2010 = 125 articles, from 2011 to 2022 = 372 articles). This line of research has shown promising results, including reducing symptoms of depression, followed by a gradual reduction and eventually cessation of medication (van Tulleken et al., 2018), increases in well-being and positive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 119 publications
0
9
0
Order By: Relevance
“…Immersion stimulates both the PNS and SNS branches. A predominant PNS is usually observed during descent and bottom stay, in accordance with human diving responses [ 49 ]. After emersion and continuation of atmospheric air breathing, the SNS takes over the PNS.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Immersion stimulates both the PNS and SNS branches. A predominant PNS is usually observed during descent and bottom stay, in accordance with human diving responses [ 49 ]. After emersion and continuation of atmospheric air breathing, the SNS takes over the PNS.…”
Section: Discussionmentioning
confidence: 91%
“…HRV monitoring during scuba diving is only available from a limited number of studies, and CCR diving seems to induce a different HRV response than OC diving [ 22 , 49 ]. Immersion stimulates both the PNS and SNS branches.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, Al Haddad et al (2010a) found that it appears to be a simple, effective and inexpensive strategy to accelerate PNS reactivation. Additionally, the potential for increasing PNS activity was shown by previous studies outside of the exercise context (Ackermann et al, 2022;Eckberg et al, 1984;Finley et al, 1979;Hayashi et al, 1997;Kinoshita et al, 2006). Still, more research should be conducted to determine if it can elicit similar effects to CWI on the PNS, even though most of the body is not actually immersed in water.…”
Section: Main Findingsmentioning
confidence: 86%
“…While this is highly dependent on the sport, in this meta‐analysis evidence for it was only found for CWI. An argument could be made for CWFI since it is easy to administer, quick, and inexpensive (Al Haddad et al, 2010a), but more research is required to understand its impact on the PNS (Ackermann et al, 2022), and its limited effects on muscular parameters need to be considered. In a professional sports environment, massage therapy is very common after exercise, and the infrastructure for it already exists, therefore thorough investigations into its effects on the PNS are also recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation